2019
DOI: 10.1093/toxsci/kfz164
|View full text |Cite
|
Sign up to set email alerts
|

The Valosin-Containing Protein Protects the Heart Against Pathological Ca2+ Overload by Modulating Ca2+ Uptake Proteins

Abstract: Stress-induced mitochondrial calcium (Ca2+) overload is a key cellular toxic effectors and a trigger of cardiomyocyte death during cardiac ischemic injury through the opening of mitochondrial permeability transition pore (mPTP). We previously found that the valosin-containing protein (VCP), an ATPase-associated protein, protects cardiomyocytes against stress-induced death and also inhibits mPTP opening in vitro. However, the underlying molecular mechanisms are not fully understood. Here, we tested our hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…In addition, a recent study has shown that an ATPase protein named valosin-containing protein (VCP) is involved in the regulation of mitochondrial Ca 2+ uptake [ 13 ]. VCP belongs to an ATPase associated family with four structural domains [ 87 ]: an N-terminal substrate-binding domain, two ATPase domains, and a C terminal domain.…”
Section: Other Regulators In Mitochondrial Ca 2+ mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, a recent study has shown that an ATPase protein named valosin-containing protein (VCP) is involved in the regulation of mitochondrial Ca 2+ uptake [ 13 ]. VCP belongs to an ATPase associated family with four structural domains [ 87 ]: an N-terminal substrate-binding domain, two ATPase domains, and a C terminal domain.…”
Section: Other Regulators In Mitochondrial Ca 2+ mentioning
confidence: 99%
“…Recently, VCP has been found to play an essential role in mitochondrial function, including mitochondrial respiration, ATP production and mPTP opening. Overexpression of the VCP protects cardiomyocyte against stimulated death and reduces the I/R induced infarct size in the heart [ 13 , 90 , 91 , 92 ]. Notably, the most recent study found that VCP protects the heart from the stress by preventing excessive Ca 2+ overload through inhibiting Ca 2+ uptake [ 13 ].…”
Section: Other Regulators In Mitochondrial Ca 2+ mentioning
confidence: 99%
See 3 more Smart Citations